Biodiversity of Birds in the Green Urban Area of Petrochemical Industry, Palembang, South Sumatra, Indonesia - Yona Selvia Arma Dewita; Hilda Zulkifli; Harmida Harmida (Program Pascasarjana Universitas Sriwijaya, 2016)
Abstract: The study on